Leadership Motivation and Competence as Key Factors for Women's Empowerment: Motivasi dan Kompetensi Pimpinan sebagai Faktor Kunci Pemberdayaan Perempuan - Ma’ruf, Hazwa Pradyfta; Rizky, M. Chaerul; Thalasagi, Bonita; Utami, Namira Azahra; Ardila, Zulfa; Rangkuti, Fahrurozy (Indonesian Journal of Innovation Studies, 2025)
General Background: Women's empowerment remains a critical component of inclusive rural development in Indonesia. Specific Background: In villages like Belawan Bahagia, the role of local leadership is essential in ensuring effective community-based empowerment initiatives. Knowledge Gap: While numerous studies address women's empowerment broadly, limited empirical evidence evaluates the influence of leadership motivation and competence at the village level. Aim: This study investigates how the motivation and competence of village leaders impact women's empowerment in Belawan Bahagia Village. Methodology: Employing a quantitative approach, the research surveyed 100 women of productive age. Data were analyzed using validity and reliability tests, normality and heteroscedasticity assessments, multiple regression analysis, as well as t- and F-tests. Results: Findings reveal that both motivation and competence of village leaders significantly and jointly influence the success of women's empowerment programs.Novelty: This study offers localized insights into how specific leadership attributes can directly enhance empowerment outcomes for rural women. Implications: The results underscore the importance of capacity building for village leaders, emphasizing motivation and competence as strategic levers to strengthen gender-focused development programs.  Highlights: Highlights the impact of leadership traits on women's empowerment. Uses quantitative methods with robust statistical analysis. Offers practical insights for improving village-level governance. Keywords: Motivation, Competence, Women's Empowerment, Village Leadership, Community Development